Circadian Plasticity of Mammalian Inhibitory Interneurons. (6th March 2017) - Jasinska, Malgorzata; Pyza, Elzbieta
Abstract : Inhibitory interneurons participate in all neuronal circuits in the mammalian brain, including the circadian clock system, and are indispensable for their effective function. Although the clock neurons have different molecular and electrical properties, their main function is the generation of circadian oscillations. Here we review the circadian plasticity of GABAergic interneurons in several areas of the mammalian brain, suprachiasmatic nucleus, neocortex, hippocampus, olfactory bulb, cerebellum, striatum, and in the retina.